Nitrogen and sulphur release dynamics and kinetics in soils incubated with sulphur-augmented nitrogen sources - Mubo, Omogoye Adewale; Akinkunmi, Akinrinde Ezekiel; Akeem, Lawal Babatunde; Iderawumi, Abdulraheem Mukhtar (Current Research in Agricultural Sciences, 2024)
The study investigated N and S release dynamics and kinetics in soils incubated with sole and sulphur-augmented N fertilizer sources to evaluate their release patterns, potentially releasable quantities, and release rate constants. 50g of soil samples (from Ibadan and Ogbomoso, Nigeria) were measured into incubation cups and treated with Cattle Manure (CM) at 90 kg Nha-1, CM at 90 kg Nha-1+sulphur powder (SP) at 30 kg Sha-1, Cocoa Pod Powder (CPP) at 90 kg Nha-1, CPP at 90 kg Nha-1+SP at 30 kg Sha-1, NPK 20-10-10 at 90 kg Nha-1, NPK 20-10-10 at 90 kg Nha-1+SP at 30 kg Sha-1 and No Fertilizer Treatment (NFT). The incubated soils were moistened with distilled water at 60% field capacity thrice per week throughout a 105-day incubation period under ambient laboratory conditions and were analysed for N and S contents at 21, 42, 63, 84, and 105 days. The experiment was a completely randomized design with three replicates. Data on N and S release were evaluated, and fitted into zero, first- and second order kinetics equations. Release dynamics of N followed the order; NPK+SP/NPK/CPP+SP/CPP>CM+SP/CM>NFT in soils of both locations, while orders of S release were CPP+SP/CPP>CM+SP>CM/NPK+SP>NPK>NFT and CPP+S/CPP/CM+SP>CM>NPK+SP>NPK>NFT in soils of Ibadan and Ogbomoso, respectively. The release of N and S conformed to zero, first, and second order kinetics with coefficients of determination (R2), ranging from 0.20 to 0.99. Therefore, soil incorporation of sole and sulphur-augmented CM and CPP could be substituted for sole and sulphur-augmented NPK 21 days before planting of N and S-demanding crops.